Quarantine waste, including recyclables, returned to Australia from Australian Antarctic stations, 2000-2013 - SHARMAN, ANDREW (hasPrincipalInvestigator); Australian Antarctic Data Centre (publisher)
This dataset was originally set up as a "State of the Environment" indicator - however, that application no longer functions at the Australian Antarctic Data Centre, so the data have been extracted and attached to this original metadata record for the indicator. INDICATOR DEFINITION This indicator records the composition and weight of waste returned to Australia from Macquarie Island, Casey, Davis and Mawson stations. For the purposes of this indicator, waste is defined as materials that are no longer wanted, needed or used and which require treatment or disposal. RATIONALE FOR INDICATOR SELECTION The data will assist Australia in meeting Article 17 of the Protocol on Environmental Protection to the Antarctic Treaty, namely, to report annually on the steps taken to implement the Protocol. This indicator will also assist in monitoring the extent to which waste minimisation is occurring, and furthering planning and policy measures appropriate to efficient and effective waste management practices. The data may be a valuable tool in evaluating the environmental impacts of operational and scientific activities, and the extent of the community adoption and economics of recycling. DESIGN AND STRATEGY FOR INDICATOR MONITORING PROGRAM Spatial scale: Australian Antarctic continental stations and Macquarie Island station. Frequency: Annual report. Measurement technique: Data (waste weight and composition) are compiled from station cargo manifests and information supplied by the AAD's waste management contractor.